Study of Thyroid and Reproductive hormones levels in fertile and infertile women - G . Magtooph , Majida (University of Thi-Qar Journal of Science, 2015)
Hormones are actual messengers in endocrine signaling. Thyroid gland as endocrine glands holds a critical place incontrolling brain and somatic development in embryos and metabolic activities in adults . There is an Coordinationbetween hypothalamus-pituitary-thyroid and hypothalamus-pituitary- gonadal axes, Therefore hypo- and hyperthyroidism affect women fertility and prolonged exposure to altered thyroid physiology could lead to women infertility . This study was done to illustrate some hormones(sex and thyroid ) changes , the study included 73 infertile women and 23 fertile women 24-35 years old between March 2013 and June 2013, in Endocrines and diabetes medical center in Nassirhyia city . The results of the study were revealed the significantly increase in the level of LH , FSH , and prolactin and T4 in infertile womens compared with fertile womens(control) while no significant differences was observed in T3 level between two groups .